Tree crop physiology - Sethuraj, M. R.; Raghavendra, A. S. (Developments in agricultural and managed-forest ecology, 1987)
This book is the result of a recommendation from the plenary session of ``TREE-PHYSINDIA-82'', an international symposium held at the Rubber Research Institute of India, Kottayam, that a publication be brought out presenting information on the methodology adopted for various physiological studies in tree crops. Containing reviews on general physiology as well as detailed information on certain selected tree crops, the choice of topics emphasizes many aspects of tree physiology. The contributed articles in Part A provide an insight into different approaches to studying the physiology of tree crops, with an emphasis on methodology. Part B provides case-histories of physiological investigations on selected economically important tropical tree crops. The volume will provide a valuable source of information and stimulus to scientists involved in the work of tree physiology.